2008
DOI: 10.1097/aco.0b013e328303bfc9
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in the treatment of lumbar radicular pain

Abstract: Treatment for lumbar radicular pain has long included epidural steroids to inhibit the inflammatory component of radicular pain. Recent studies have more precisely identified the cytokines responsible for this inflammatory process and indicate that inhibition of these cytokines may offer more specific and effective treatment for lumbar radicular pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Methotrexate was used in only 2 animal model studies . Of the five prior review articles, only one was a systematic review, which was focused primarily on the clinical efficacy of anti‐TNF drugs for LBP . As none of the reviewed trials employed any form of DMARD combination, the results are grouped further under the subheadings of the DMARD used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methotrexate was used in only 2 animal model studies . Of the five prior review articles, only one was a systematic review, which was focused primarily on the clinical efficacy of anti‐TNF drugs for LBP . As none of the reviewed trials employed any form of DMARD combination, the results are grouped further under the subheadings of the DMARD used.…”
Section: Resultsmentioning
confidence: 99%
“…Disagreements were resolved by mutual consensus. Of the 346 articles retrieved, 34 publications met the inclusion criteria and were further reviewed . The study analysis focused on the specific drug used, dose and mode of drug administration, efficacy of the drug, any safety measures adopted for the novel drug use, and the adverse effects reported.…”
Section: Methodsmentioning
confidence: 99%
“…Given the patient's severe low-back pain and its radicular component, we speculated that the symptoms were potentially the manifestation of nerve root irritation due to not only compression but also release of inflammatory cytokines in the perivascular space. 4,5,10,16 Thus, the patient was started on a short tapering course of dexamethasone, with the understanding that dexamethasone could theoretically exacerbate the symptoms because it can lead to increased intravascular volume. Furthermore, the patient was admitted to the neurosurgical intensive care unit for close monitoring.…”
Section: Case Reportmentioning
confidence: 99%
“…Infliximab (and other selective anti‐TNF drugs, e.g., etanercept) has been used to treat lumbar radicular pain including severe sciatica [156–160] and rheumatoid arthritis [161]. Analysis of blister fluid from CRPS‐affected limbs of two patients indicated that local concentrations of TNF and IL‐6 were significantly decreased following selective anti‐TNF (infliximab) treatment.…”
Section: Is Tnf a Useful Target For Treating Crps?mentioning
confidence: 99%